2011
DOI: 10.1038/ijo.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity at childhood predicts changes in total and central adiposity over a 6-year period

Abstract: Objective: To examine the associations of insulin resistance at childhood with adiposity changes over a 6-year period (from 9 to 15 years) in a sample of 659 Swedish and Estonian children (52.7% girls) participating in the European Youth Heart Study. Research, Design and Methods: We measured weight, height, waist circumference, biceps, triceps, subscapular, suprailiac, and medial calf skinfolds, and we calculated body mass index (BMI), sum of five skinfolds, and body fat percentage. Fasting plasma glucose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…( 13 ) , breakfast skipping was associated with high fasting insulin. High fasting insulin may contribute to central obesity ( 32 ) . An experimental study by Pereira et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 13 ) , breakfast skipping was associated with high fasting insulin. High fasting insulin may contribute to central obesity ( 32 ) . An experimental study by Pereira et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the short-term randomized crossover trial by Farshchi et al (13) , breakfast skipping was associated with high fasting insulin. High fasting insulin may contribute to central obesity (32) . An experimental study by Pereira et al suggests that breakfast skipping, as well as breakfast quality, may have important effects on factors related to appetite control and glycaemic control (20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the CARDIA study examined 3095 young adults followed up for 7 years and found that an increase of 5 uU/ml in fasting insulin predicted a 5 kg/m 2 increase in BMI after adjustment for race and gender [ 9 ]. Another relatively large sample size study reported that HOMA-IR significantly predicted total and central adiposity increased after 6 years follow-up in the Swedish children[ 11 ]. Johnson et al showed that increased fat mass were significantly associated with fasting insulin concentrations in a cohort of 83 Caucasian and 54 African children[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…El PBN se ha relacionado con un incremento en la ganancia de masa grasa y esto es independiente del IMCz 31 . En el presente estudio no se encontraron diferencias significativas en el peso al momento del estudio, pero sí se observó una tendencia a mayor CC en el grupo de niños con antecedente de PBN.…”
Section: Discussionunclassified